Justification of the necessity of knowledge management convergence in multinational projects - Sharovara, Olena (КНУБА, 2019)
Over the past decade, major projects typically involve professionals from all over the world, expanding the scope of competencies that a project manager must have. Multinational project teams and the creation of virtual project teams are the norm in a modern globalized economy. The transition from project management, in which the entire team is local, to the management of teams covering different time zones and nationalities becomes a new challenge. Globalization researcher K. Omaye considers that globalization is an irreversible process that deprives the traditional notions of national politics, trade, and citizenship. In this sense, in his opinion, the economic nationalism of individual states has now become meaningless. The formation of a single global meta-space (which is influenced by PESTLE factors) for free and effective business on an international scale becomes an urgent need. However, every single common global space based on the action of the principle of universality. A fundamental scientific problem arises – creation of an adequate model of convergent knowledge management in multinational projects, describing the process of scientific and innovative development of society at all its stages and levels. Considered from a rational and empirical approach what is important in the knowledge management is their functionalist perspective, because it allows to know about the rational world while integrates the disciplines and individuals as substantial components of multinational projects. There is a need to convert different intellectual resources into shared knowledge platform within a project to deliver better-customized services. Current efforts in managing knowledge have concentrated on producing; sharing and storing knowledge while projects require the combined use of these intellectual resources to enable organizations to provide innovative and customized services and deliver projects successfully. A review of the literature and research evaluations published by the researchers were made to justify the necessity of Knowledge Management Convergence in Multinational Projects.
Keywords: Knowledge Management; Convergence; Multinational Projects; knowledge; information; data; the department project management